2014
DOI: 10.2134/jeq2013.06.0230
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Phosphorus in Runoff from Cattle Manure Compost Windrows of Different Maturities

Abstract: Manure composting has become commonplace in the beef cattle ( L.) feedlot industry in Alberta. However, the nitrogen (N) and phosphorus (P) characteristics of runoff from windrows subjected to heavy rainfall at different compost maturities are unknown. On Days 18, 26, 40, 54, 81, 109, and 224 of composting, a rainfall simulator generated runoff, which was collected in timed 5-L increments, creating the variable "time during runoff event" (TDRE). The volumetric runoff coefficient of windrows increased from 24% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…The rainfall simulator was calibrated for a rainfall intensity of 98 mm h −1 . Comparable rainfall intensities have been used in previous rainfall simulation studies investigating nutrient runoff (Reiter et al, 2013; Wang et al, 2013a; Larney et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…The rainfall simulator was calibrated for a rainfall intensity of 98 mm h −1 . Comparable rainfall intensities have been used in previous rainfall simulation studies investigating nutrient runoff (Reiter et al, 2013; Wang et al, 2013a; Larney et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Most nutrients showed increasing concentrations with runoff volume as occurred with chlortetracycline in runoff from the bedding area of feedlot pens (Sura et al, 2015). Other nutrients, notably NO 3 -N (Larney et al, 2014a), showed decreasing concentrations with runoff volume, as occurred with tylosin after collection of the second liter of runoff on Day 2.…”
Section: Antimicrobial Concentrations In Runoffmentioning
confidence: 93%
“…Thus, concentrations of the three antimicrobials would be expected to be greater in the leachate compared with the corresponding concentrations in the runoff. Other workers (Coker, 2008;Larney et al, 2014a) have indicated that contaminant concentrations in leachate were greater than those in surface runoff.…”
Section: Antimicrobial Concentrations In Runoffmentioning
confidence: 96%
See 2 more Smart Citations